Oxyresveratrol: Sources, Productions, Biological Activities, Pharmacokinetics, and Delivery Systems - Likhitwitayawuid, Kittisak (Molecules, 2021)
Oxyresveratrol has recently attracted much research attention due to its simple chemical structure and diverse therapeutic potentials. Previous reviews describe the chemistry and biological activities of this phytoalexin, but additional coverage and greater accessibility are still needed. The current review provides a more comprehensive summary, covering research from 1955 to the present year. Oxyresveratrol occurs in both gymnosperms and angiosperms. However, it has never been reported in plants in the subclass Sympetalae, and this point might be of both chemotaxonomic and biosynthetic importance. Oxyresveratrol can be easily obtained from plant materials by conventional methods, and several systems for both qualitative and quantitative analysis of oxyresveratrol contents in plant materials and plant products are available. Oxyresveratrol possesses diverse biological and pharmacological activities such as the inhibition of tyrosinase and melanogenesis, antioxidant and anti-inflammatory activities, and protective effects against neurological disorders and digestive ailments. However, the unfavorable pharmacokinetic properties of oxyresveratrol, including low water solubility and poor oral availability and stability, have posed challenges to its development as a useful therapeutic agent. Recently, several delivery systems have emerged, with promising outcomes that may improve chances for the clinical study of oxyresveratrol.